Nuclear Factor Erythroid-2-Related Factor 2 Signaling in the Neuropathophysiology of Inherited Metabolic Disorders - Seminotti, Bianca; Grings, Mateus; Tucci, Paolo; Leipnitz, Guilhian; Saso, Luciano (Frontiers in Cellular Neuroscience, 2021)
Inherited metabolic disorders (IMDs) are rare genetic conditions that affect multiple organs, predominantly the central nervous system. Since treatment for a large number of IMDs is limited, there is an urgent need to find novel therapeutical targets. Nuclear factor erythroid-related factor 2 (Nrf2) is a transcription factor that has a key role in controlling the intracellular redox environment by regulating the expression of antioxidant enzymes and several important genes related to redox homeostasis. Considering that oxidative stress along with antioxidant system alterations is a mechanism involved in the neuropathophysiology of many IMDs, this review focuses on the current knowledge about Nrf2 signaling dysregulation observed in this group of disorders characterized by neurological dysfunction. We review here Nrf2 signaling alterations observed in X-linked adrenoleukodystrophy, glutaric acidemia type I, hyperhomocysteinemia and Friedreich’s ataxia. Additionally, beneficial effects of different Nrf2 activators are shown, identifying a promising target for treatment of patients with these disorders. We expect that this article stimulates research into the investigation of Nrf2 pathway involvement in IMDs and the use of potential pharmacological modulators of this transcription factor to counteract oxidative stress and exert neuroprotection.